2020
DOI: 10.1111/jon.12727
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Cerebral and Extracerebral Pathologies on Apparent Diffusion Coefficient Values in the Fetal Brain

Abstract: The changing MRI signal accompanying brain maturation in fetal brains can be quantified on apparent diffusion coefficient (ADC) maps. Deviations from the natural course of ADC values may reflect structural pathology. The purpose of this study was to determine the influence of fetal pathologies on the ADC values in different regions of the fetal brain and their evolution with increasing gestational age. METHODS: This was a retrospective study of 291 fetuses evaluated between the 14th and the 40th week of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
4
8
0
Order By: Relevance
“…This myelination process causes significant reduction in RD, balanced by a slower decrease in AD due to the disappearance of cytoplasmic arborization. This evolution of DTI values has also been reported by other studies 37–43 .…”
Section: Diffusion Tensor Imaging Of Normal Brain Developmentsupporting
confidence: 90%
“…This myelination process causes significant reduction in RD, balanced by a slower decrease in AD due to the disappearance of cytoplasmic arborization. This evolution of DTI values has also been reported by other studies 37–43 .…”
Section: Diffusion Tensor Imaging Of Normal Brain Developmentsupporting
confidence: 90%
“…Numerous studies have reported that ADC values in the cerebral parenchyma could re ect differences in brain maturation and foetal brain growth [15,23,24]. In our study, the ADC differences between the cerebellar dysplasia and malformation groups did not differ signi cantly.…”
Section: Discussionsupporting
confidence: 39%
“…In the group with GA $ 26 weeks, our results corroborate previous abnormal ADC values in a smaller cohort of 3 fetuses with CHD with a mean GA of 34 weeks, reported by Berman et al, 14 who found that the ADC values of the thalamus in the CHD group were significantly higher than those in the control group; however, the values in the basal ganglia were not significantly different. Schönberg et al 15 also described ADC values in 8 fetuses affected by CHD with a mean GA of 32.5 weeks and found an increase in ADC values in all regions of the WM as well as in the basal ganglia, comparable with values found in healthy fetuses. In fetuses with CHD of ,26 weeks' GA, our results showed a significant reduction in the ADC values of the WM and pons compared with the control group.…”
Section: Discussionmentioning
confidence: 68%
“…Another source of the difference is that the types of CHD included in the cohort study were diverse. Of note, these previous findings 14,15 in regional tissue development were associated with a more specific type of complex CHD: HLHS. However, other CHD types with decreased oxygen delivery to the brain can also be associated with prenatal neurologic injury.…”
Section: Discussionmentioning
confidence: 73%